Abandonul şcolar - Bonea, Georgiana Virginia (Calitatea Vieții, 2019)
The main objective of this study is to analyze the situation of school abandonment in Romania, by classes, residence and gender. Also, the individual, school, social and economic factors that influence the pupil to leave school are followed. School abandonment is more a process and less an event in itself. Social inclusion and equal opportunities are the main solutions to tackling this social problem. Early school abandonment is both an individual problem and of the society as a whole, which is why social prevention and target policies need to be carefully considered. Also, an increased attention is paid to schools of arts and crafts, which have a major influence on the prevention and preventing school dropout.